Informality, economic complexity, and internalization of rules - Laguna, Marcen; Hernández, Iván; Godoy, Jesús María (Frontiers in Sociology, 2023)
This research aimed to find out the relationship between informality and the internalization of the rules of behavior required for complexity in the economic system, as better knowledge is required for formalization policy to have a greater impact. We use the economic complexity index (ECI) for 2018 at the regional level in Colombia, which combines the country's productive structure with the amount of knowledge and know-how embodied in the goods it produces. The informality measure we use is the individual's affiliation to social security (in particular health insurance), and we use a proxy of civic rule's internalization as an inverse relation with traffic tickets. This research aimed to shed new light on public policy to improve formalization and its economic impact. First, we include a theory that includes both intrinsic and extrinsic motivation types. The self-determination theory or organismic integration theory proposes this theory. Second, we have argued that the motivation to formalize is intrinsic to greater cultural capacity. Individuals gradually internalize rules of behavior that have repercussions on social dynamics. Third, the composition and characteristics of the families in the study sample seem to show that some factors increase the propensity for informality. Our empirical analysis reveals that group of people with a lower educational level are the ones who are more likely to belong to the informal labor market. These results are consistent with the literature. Multivariate Probit regression was used to examine these factors.